Telaah Kitab Al-Kashfu wa Al-Bayan ‘An Tafsir Al-Qur’an Karya Imam Al-Tha’labi - Hibatullah, Alif (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2023)
In the historical development of the interpretation of the Qur'an, many previous and contemporary scholars have focused their attention in this field. With a variety of distinctive styles and methods used also vary. One of them is imam al-Tha’labī ā whose full name is Aḥmad Ibn Muḥammad Ibn Ibrāhīm al-Naisabūrī al-Shāfi’ī ā Abū Isḥāq al-Tha’labī ā, he is an expository figure who has high integrity values in his time. This research method is a literature review type and analyzes data descriptively. Many works were produced, one of the monumental works of Imam al-Tha’labī ā in the discipline of interpretation is the book entitled al -Kashfu wa al -Bayān ‘ An Tafsīr al - Qur'ān . Departing from an in-depth study of the previous exegetical books and on the basis of his motivation to reject the interpretations of the heretical and Mu'tazilah scholars. The style or interpretation model used by imam al-Tha’labī ā is a technique of taḥlīlī ā and Muqaraṇ ī ā, as well as the method used is the bi al-Ma’thūr interpretation method. While the systematics of writing his commentary, imam al-Tha’labī ā first explained about the sūrah to be interpreted, whether it was classified as a makkīyah sūrah or madanīyyah sūrah. Second, explaining the number of letters contained accompanied by the number of sentences contained in the sūrah ending with the number of verses. third, include a history of ḥadīth regarding the virtues of the sūrah to be interpreted, written in full with the narrators. Finally, in reviewing one interpretation of the verse interpreted by imam al-Tha’labī ā, he enriches his point of view by citing several views of other commentators, so that the treasures of interpretation given are very comprehensive, and the interesting point here is the interpretation of the majority of scholars which is used as a cover by the imam al-Tha’labī ā.